Prevention of Acute Myocardial Infarction and Stroke among Elderly Persons by Dual Pneumococcal and Influenza Vaccination: A Prospective Cohort Study - Hung, Ivan F. N.; Leung, Angela Y. M.; Chu, Daniel W. S.; Leung, Doris; Cheung, Terence; Chan, Chi-Kuen; Lam, Cindy L. K.; Liu, Shao-Haei; Chu, Chung-Ming; Ho, Pak-Leung; Chan, Sophia; Lam, Tai-Hing; et al. (Clinical infectious diseases, 2010)
Background. DespiteWorld Health Organization recommendations, the rate of 23-valent pneumococcal (PPV) and influenza (TIV) vaccination among elderly persons in Hong Kong, China, is exceptionally low because of doubts about effectiveness of vaccination. The efficacy of dual vaccination remains unknown. Methods. From 3 December 2007 to 30 June 2008, we conducted a prospective cohort study by recruiting outpatients aged ⩾65 years with chronic illness to participate in a PPV and TIV vaccination program. All were observed until 31 March 2009. The outcome of subjects, including the rates of death, hospitalization, pneumonia, ischemic stroke, acute myocardial infarction, and coronary and intensive care admissions, were determined. Results. Of the 36,636 subjects recruited, 7292 received both PPV and TIV, 2076 received TIV vaccine alone, 1875 received PPV alone, and 25,393 were unvaccinated, with a duration of follow-up of 45,834 person-years. Baseline characteristics were well matched between the groups, except that there were fewer male patients in the PPV and TIV group and fewer cases of comorbid chronic obstructive pulmonary disease among unvaccinated persons. At week 64 from commencement of the study, dual-vaccinees experienced fewer deaths (hazard ratio [HR], 0.65; 95% confidence interval [CI], 0.55–0.77]; P <.001) and fewer cases of pneumonia (HR, 0.57; 95% CI, 0.51–0.64; P<.001), ischemic stroke (HR, 0.67; 95% CI, 0.54–0.83; P<.001), and acute myocardial infarction (HR, 0.52; 95% CI, 0.38–0.71; P<.001), compared with unvaccinated subjects. Dual vaccination resulted in fewer coronary (HR, 0.59; 95% CI, 0.44–0.79; P<.001) and intensive care admissions (HR, 0.45; 95% CI, 0.22–0.94; P = .03), compared with among unvaccinated subjects. Conclusions. Dual vaccination with PPV and TIV is effective in protecting elderly persons with chronic illness from developing complications from respiratory, cardiovascular, and cerebrovascular diseases, thereby reducing hospitalization, coronary or intensive care admissions, and death.